Mapping the Evolution of Islamic Da’wah in Indonesia: A Bibliometric Analysis and Future Research Directions - Choirin, Muhammad; Mardhiah, Ainal; Bahri, Saiful; Hadiyan, Hadiyan; Yumna, Laila (Jurnal Ilmiah Peuradeun, 2025)
This study examines the evolution of research related to Islamic da’wah in Indonesia, sourced from reputable Scopus-indexed journals from 1995 to 2023. It explores author productivity and related keywords that depict Islamic da’wah’s development in Indonesia. This research employs bibliometric analysis techniques and descriptive statistical approaches, utilizing the biblioshiny tool and R program to identify recommended research keywords with significant potential for future development. The research findings indicate that “social media” emerges as a frequently occurring keyword in studies on Islamic da’wah in Indonesia. Furthermore, two research paths emerge as recommendations for future development: the authority of Islamic da’wah in Indonesia and Islamic da’wah in the digital era. This investigation holds significant importance for stakeholders, including government authorities, Muslim preachers (da’i), and Muslim scholars, as it provides fundamental insights into the development of Islamic da’wah literature in Indonesia, thus offering prospective research directions.